Funkcjonowanie elektronicznych biur podawczych w wybranych krajach - Materla, Anna (Wydawnictwo C.H. Beck, 2017)
The aim of this paper is to present solutions that have been adopted in chosen European countries (Germany, Italy and France) in order to build an electronic incoming correspondence log in regard to civil proceedings. Despite the fact that basic provisions concerning electronic documents, electronic signatures and alternatively use of electronic means have been already implemented for many years, courts were not adjusted to the requirements of electronic incoming correspondence logs and also participants of the civil proceedings were reluctant to use this option, because they were unsure about this form of e-justice. For a proper functioning of an electronic incoming correspondence log, an IT system has to be designed and implemented, but the existing systems in described countries were only regional systems or could not be used in every court. In order to solve those problems, Germany, Italy and France decided to improve or rebuilt their electronic incoming correspondence logs and at least partly adopt an obligation to the professionals to use this system. This article presents amendments concerning the use of electronic communication with courts in the legal provisions in chosen countries. An outcome of the article may be some possible solutions for other jurisdictions on how to deal with various problems concerning implementation of an electronic incoming correspondence log.
Keywords: electronic incoming correspondence log; electronic filing of documents to the court; IT systems in judiciary; e-justice in civil proceedings; civil proceedings